2018
DOI: 10.1021/acs.jafc.7b04236
|View full text |Cite
|
Sign up to set email alerts
|

Novel Folate Binding Protein in Arabidopsis Expressed during Salicylic Acid-Induced Folate Accumulation

Abstract: Increasing the quantity of natural folates in plant foods is recently gaining significant interest, owing to their acute deficiencies in various populations. This study observed that foliar salicylic acid treatment enhanced the accumulation of folates in Arabidopsis, which correlated with the increase in a folate binding protein (FBP) and the expression of mRNA of a putative folate binding protein At5G27830. A protein band corresponding to ∼43 kDa was observed after resolving the affinity-purified protein on S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…A proof-of-concept for this methodology is the engineering of high-folate rice lines with enhanced stability achieved through the ectopic expression of a mammalian folatebinding protein (Blancquaert et al, 2015). Similarly, plant vitaminbinding proteins could be employed, as these have been proposed to exist for folates (Puthusseri et al, 2018) and thiamine (Shimizu et al, 1990;Gunarti et al, 2020). Second, increasing cellular vitamin sequestration by creating a metabolic sink could be used to increase vitamin stability.…”
Section: Genetic Engineeringmentioning
confidence: 99%
“…A proof-of-concept for this methodology is the engineering of high-folate rice lines with enhanced stability achieved through the ectopic expression of a mammalian folatebinding protein (Blancquaert et al, 2015). Similarly, plant vitaminbinding proteins could be employed, as these have been proposed to exist for folates (Puthusseri et al, 2018) and thiamine (Shimizu et al, 1990;Gunarti et al, 2020). Second, increasing cellular vitamin sequestration by creating a metabolic sink could be used to increase vitamin stability.…”
Section: Genetic Engineeringmentioning
confidence: 99%
“…The six hydrogen bonds holding the SiFBP to FA were formed at Gln 182 , Arg 276 , Ser 184 , Thr 186 , Glu 241 , and Lys 270 (Figure S2a–c). Previously, a report on AtFBP revealed that it could bind folic acid with a free energy change (Δ G ) of −9.3 according to molecular docking analysis . The three-dimensional model through the protein homologous alignment between SiFBP and AtFBP showed that they have similar spatial configuration (Figure S2d).…”
Section: Resultsmentioning
confidence: 96%
“…Overexpression of the bovine FBP gene in rice significantly enhanced the folate content and stability and led to the “second-generation” of folate-biofortified rice, the grains of which contain up to 500 μg of folates per100 g fresh weight . The FBP gene in Arabidopsis was first reported and suggested to bind folates through in vitro studies . However, there has been little research on the functional diversity of FBP genes in plants.…”
Section: Introductionmentioning
confidence: 99%
“…The medium that did not stick to folic acid was blocked by the addition of ethanolamine 1 M pH 7.2 for two hours at room temperature and washed 2-3 times with 0.02 phosphate buffer saline pH 7.2 containing 0.1 M NaCl. [17,18] DEAE-cellulose ion exchange chromatography fractions pH was changed to be 3 by adding H3PO4 1M solution and followed by acetate buffer pH 3.5 to separate folate from FBP. It was run the following the protocol.…”
Section: Purification Of Affinity Chromatographymentioning
confidence: 99%